Close Corporations and the Criminal Law: On “Mom and Pop” and a Curious Rule - Kathleen F. Brickey (Washington University Law Quarterly, 1993)
Established principles governing corporate criminal liability apply indiscriminately to all corporations, regardless of size or corporate form. Yet to date, little consideration has been given to the question whether the reasons supporting recognition of corporate liability for crime apply with equal force to close corporations. Nor has the question whether the same sentencing rules should apply to close corporations and their publicly held counterparts been addressed. Hence, this Article journeys off the beaten path to explore these intersecting themes.
Keywords: Close corporations; Criminal liability of juristic persons; Sentences (Criminal procedure)